Optimasi Sawah Bukaan Baru Lahan Rawa Pasang Surut di Kabupaten Bulungan - Muhamad Hidayanto; Yossita Fiana (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2021)
Indonesian swamp has a high potency to provide areas for agricultural expansion, which means to raise food security. To optimize its utilization, government has developed new rice fields in the tidal swamp. This research was carried out in a new rice field from the tidal swamp in Bulungan District. The research aimed to optimize the new rice fields by implementing superior rice varieties (NSV). The study used a randomized block design (RBD) with three replicates. Benefit Cost Ratio (BCR) analysis was performed to determine the feasibility of rice farming in the new field. The NSV consisted of six varieties of rice, namely Inpara-1, Inpara-2, Inpara-3, Inpara-4, Inpara-5, and a local variety. The planting pattern implemented was jajar legowo (jarwo) 2:1, and seedlings were planted three stems per clump at the age of 20-25 days. Each planting treatment was given the same dose of limestone and fertilizer, namely dolomite 1,000 kg ha-1, NPK fertilizer 250 kg ha-1, and Urea 100 kg ha-1. The results showed that all varieties were able to adapt tidal swamp condition, and Inpara varieties productivity was higher than that of local variety. The productivity of superior varieties rice in a newly opened rice reached 2.6–5.75 tons milled dry grain ha-1. The findings also revealed that superior rice varieties have BCR>1, while the local variety had BCR<1. The productivity of Inpara-1 and Inpara-2 was the highest compared to other varieties and was also feasible to be cultivated on newly opened rice fields in Bulungan District.